Environmental Mapping and Utilization as a Geography Learning Resource at Senior High School - Dhi Bramasta; Ana Andriani (JAMBURA GEO EDUCATION JOURNAL, 2026)
Local environments provide meaningful learning resources for geography education by enabling students to connect geographic concepts with real-world spatial phenomena. This study examines the spatial distribution of environmental learning resources, their utilization in geography instruction, and the teaching methods applied at State Senior High School 1 Purwokerto. The study employed a mixed-methods design that integrated GIS-based spatial analysis with an exploration of teachers’ instructional practices and experiences. Data were collected through interviews, observations, and document analysis, and were analyzed using an interactive qualitative model combined with nearest neighbor analysis in ArcGIS 10.4. The findings identified 11 main learning resource locations across Banyumas Regency representing natural, social, and cultural environments. These locations were found to have a random spatial distribution; however, their use in instruction was determined mainly by relevance to learning materials, accessibility, and safety rather than geographic proximity. Teachers utilized the environment through observation, interviews, environmental analysis, basic mapping activities, and disaster simulation. The instructional approaches included field study, Project-Based Learning, Problem-Based Learning, and discovery learning, all of which promoted active, collaborative, reflective, and scientific learning. The study highlights the importance of integrating spatial analysis and environment-based pedagogy in developing contextual geography learning resources at the secondary school level